2015
DOI: 10.4103/0975-7406.163509
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health on the Net seal label and DISCERN as content quality indicators for patients seeking information about thumb sucking habit

Abstract: Aims:The aim of this study was to evaluate the reliability of websites on the thumb sucking habit using DISCERN instrument and Health on the Net (HON) seal code at a single moment in time.Subjects and Methods:An Internet search engine (www.google.com) was used to identify websites comprising information on “thumb sucking habit.” Of over 204,000 links for thumb sucking habit, the first 100 were analyzed in detail. After excluding discussion groups, news and video feeds, and removing carbon copy sites, only 36 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Due to the importance of internet health searches nowadays for health personnel and nonhealth personnel, scoring systems or quality evaluation tools have been developed as a set of indicators applied to a website to provide a quality score. The most used scoring systems nowadays are the Health on the Net Foundation Code of Conduct (HONcode), the Journal of the American Medical Association (JAMA) benchmarks, and the DISCERN instrument [5][6][7]. Eysenbach et al [8], reported that 70% of websites presenting care information had significant quality issues.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of internet health searches nowadays for health personnel and nonhealth personnel, scoring systems or quality evaluation tools have been developed as a set of indicators applied to a website to provide a quality score. The most used scoring systems nowadays are the Health on the Net Foundation Code of Conduct (HONcode), the Journal of the American Medical Association (JAMA) benchmarks, and the DISCERN instrument [5][6][7]. Eysenbach et al [8], reported that 70% of websites presenting care information had significant quality issues.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the DISCERN toolkit was used to evaluate the quality of information on websites as reported in the previous studies. 13,22,23 According to the results of the DISCERN analysis of the present study, the information on websites regarding treatments of traumatic dental injuries was limited and deficient in terms of reliability and quality. Our findings were in accordance with the previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…It is important to guide patients and guide people on dental treatment possibilities. It was stated that dentists could provide patients with appropriate information by referring patients to approved websites, for example on the thumb sucking habit ( 18 ). When the latter was evaluated the reliability of websites on the thumb sucking habit by the DISCERN tool, the highest points obtained from 36 websites was 55 out of 80, and the lowest points was 16 out of 80.…”
Section: Discussionmentioning
confidence: 99%